2017
DOI: 10.1186/s13027-017-0147-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electrochemotherapy on human herpesvirus 8 kinetics in classic Kaposi sarcoma

Abstract: BackgroundElectrochemotherapy (ECT) has shown to be an effective treatment for cutaneous and subcutaneous Kaposi sarcoma (KS) lesions. However, no study has investigated the impact of ECT treatment on the kinetics of human herpesvirus type 8 (HHV8), which is considered the necessary causal agent of KS. We aimed to evaluate HHV8 viral load and expression levels in patients affected by classic KS who received one or more ECT treatments and have been followed semi annually for up to four years.MethodsA total of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…Patients with stable or progressive disease were not reported. The reported CR rate after a single ECT session was 60.9% as reported by Curatolo et al (11) and 74.1% in the study by Starita et al (13). Moreover, Latini et al (12) reported 88.9% CR rate after the first ECT session.…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations
“…Patients with stable or progressive disease were not reported. The reported CR rate after a single ECT session was 60.9% as reported by Curatolo et al (11) and 74.1% in the study by Starita et al (13). Moreover, Latini et al (12) reported 88.9% CR rate after the first ECT session.…”
Section: Resultsmentioning
confidence: 80%
“…Five full texts were examined following screening of the titles and abstracts. Following assessment of the latter, three studies were included in the analysis (11)(12)(13). One record, which was a letter to the editor, was excluded and the secondary title partially reported on patients was subsequently included in another study from the same centre.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical experience is sparse [212][213][214][215][216][217][218][219][220][221][222] . However, small tumor size, superficial location, and prominent vascularization make Kaposi's sarcoma an ideal target for ECT, by allowing its antivascular effect to be exploited [47] .…”
Section: Soft Tissues Sarcomasmentioning
confidence: 99%